The Effect of Emotional Intelligence and Work Motivation on Employee Performance with Organizational Commitment as an Intervening Variable at the Sub-District Office of East Binjai - Maqhfira Pratiwi; Muhammad Isa Indrawan; Kiki Farida Ferine (CV. Doki Course and Training, 2026)
This study aimed to examine the effects of emotional intelligence and work motivation on employee performance, with organizational commitment as an intervening variable, at the East Binjai Sub-District Office, Binjai City, North Sumatra, Indonesia. The study employed a quantitative associative research design and involved all 76 employees as respondents using a saturated sampling technique. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the assistance of SmartPLS version 3.3.3. The measurement model demonstrated adequate validity and reliability, as all indicators met the criteria for convergent and discriminant validity, and the composite reliability values exceeded the recommended threshold of 0.70. The structural model results indicate that emotional intelligence does not have a significant direct effect on employee performance (β = 0.073; t = 0.966; p > 0.05), nor does work motivation show a significant direct influence on performance (β = 0.037; t = 0.960; p > 0.05). However, emotional intelligence has a strong and significant positive effect on organizational commitment (β = 1.033; t = 21.511; p < 0.001), while work motivation does not significantly affect organizational commitment. Furthermore, organizational commitment has a significant positive effect on employee performance (β = 0.891; t = 13.633; p < 0.001). The indirect effect analysis reveals that organizational commitment significantly mediates the relationship between emotional intelligence and employee performance, whereas it does not mediate the relationship between work motivation and performance. These findings suggest that improvements in employee performance are more effectively achieved through strengthening emotional intelligence that fosters organizational commitment rather than relying solely on work motivation.